2008
DOI: 10.1111/j.1460-9592.2008.02636.x
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil for percutaneous intravenous central catheter placement in preterm infant: a randomized controlled trial

Abstract: Low-dose remifentanil has a measurable, synergic analgesic effect in combination with 12% sucrose and non-nutritive sucking, but does not make PICC easier or quicker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…These results corroborate previous studies that evaluated interventions for sedation and analgesia during PICC insertion in neonates (7,(14)(15)19) . There are probably other factors in addition to movement of the extremities, such as the conditions of the venous system and professional experience, which have some relation to the degree of ease of performing the procedure and the duration of procedure.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results corroborate previous studies that evaluated interventions for sedation and analgesia during PICC insertion in neonates (7,(14)(15)19) . There are probably other factors in addition to movement of the extremities, such as the conditions of the venous system and professional experience, which have some relation to the degree of ease of performing the procedure and the duration of procedure.…”
Section: Discussionsupporting
confidence: 82%
“…The results showed that pain scores were lower in the group that received remifentanil 0.03 mcg/kg/min and 0.3 mL of 12% sucrose orally and nonnutritive sucking in comparison with the control group, which received only 0.3 mL of 12% sucrose orally and non-nutritive sucking two minutes before the procedure during skin preparation. It was concluded that low-dose remifentanil (0.03 mcg/kg/min) has a measurable, synergic analgesic effect in combination with 12% sucrose and nonnutritive sucking in preterm newborns, but does not make PICC insertion easier or quicker (14) .…”
Section: Discussionmentioning
confidence: 99%
“…94 Remifentanil, a shorter-acting fentanyl derivative, may be an alternative for short-term procedures and surgeries because it is not cleared by liver metabolism, but there are no studies examining its long-term effects. 95,96 Benzodiazepines, most commonly midazolam, are frequently used in the NICU for sedation. However, because there is evidence of only minor additional analgesic effect, they may not provide much benefit.…”
Section: Opioids Benzodiazepines and Other Drugsmentioning
confidence: 99%
“…Remifentanil decreased pain for PICC insertion (169) Thoracic rigidity requiring muscle blocker injection (alfentanil 20 g/kg) (167). Same time to complete the maneuver and procedure time as placebo (169) Acetaminophen Ն37 wks GA No effect for heel lance (170) Good hepatic tolerance (149) Ketamine Ineffective for tracheal suctioning (125) No cerebral hemodynamic adverse effect (5 mg/kg) (124) Repetitive painful stimuli may persistently alter pain processing in humans (171), and epidemiologic studies have revealed an association between peri-and neonatal complications and behavioral/emotional problems in childhood, anxiety/ depression, and even suicidal tendencies (172,173).…”
Section: Remaining Urgent Questions and Perspectivesmentioning
confidence: 99%